Analysis of phytosterols encapsulated in pegylated liposomes - Joanna Igielska-Kalwat; Magdalena Rudzińska; Anna Grygier; Dominik Kmiecik; Katarzyna Cieślik-Boczula; Krzysztof Dwiecki; Wojciech Smułek (Scientific Reports)
Abstract Dipalmitoylphosphatidylcholine (DPPC) lipids were encapsulated in PEGylated liposomes with free stigmasterol (ST), stigmasterol myristate (ME), and stigmasterol oleate (OE). Their quality was assessed using TEM, zeta potential, and hydrodynamic diameter measurements. The liposomes were heated to 60 °C and 180 °C. The degradation of stigmasterol and fatty acids was considered, as was derivative formation. The results show that the liposomes fulfilled their intended function. The ST liposomes were smallest, while the ME liposomes were similar in size to the OE liposomes. The degree of degradation of the compounds encapsulated in the liposomes depended on their structure. After heating the samples to 60 °C, the extent of stigmasterol degradation ranged from 3.5% in ST to 4.3% in ME and 6.5% in OE. After heating to 180 °C, the lowest level of stigmasterol degradation was observed for OE (7.3%), while degradation in ST and ME reached 13.4% and 10.1%, respectively. The high level of oxyphytosterols in all samples heated to 180 °C raised concerns. The oxyphytosterol (SOP) content of the liposomes heated to 60 °C ranged from 23.2 mg/g in those with free stigmasterol to 6.3 mg/g and 6.4 mg/g in the liposomes with stigmasterol myristate and stigmasterol oleate, respectively. After heating to 180 °C, the total SOP content was significantly higher, ranging from 88.7 mg/g for OE to 7.4 and 29.6 mg/g for ME and ST, respectively.